Enhancing Open Loop Beamsteering Performance for the Uplink of UMTS/HSPA+ under Discontinuous Transmission - Schröter, Simon; Rieß, Steffen; Weigel, Robert; Fischer, Georg (IEEE Radio and Wireless Symposium (RWS), 2014)
So called open loop transmit diversity algorithms for the uplink of UMTS use the power control commands as feedback to iteratively determine the antenna weights. The algorithms presented in literature so far are designed for continuous transmission. The UMTS standard, however, also allows discontinuous uplink transmission (DTX), which impairs the performance of these algorithms. This paper studies these impairments and proposes a method to design transmit diversity algorithms with improved performance in a DTX scenario. With such improved algorithms, the transmit power gain is 1.4 dB in DTX, which is an improvement of 0.7 dB over conventional non-DTX diversity algorithms.
elib2cris::1512001600,schroeter2014